Commensal Microbiota Contributes to Chronic Endocarditis in TAX1BP1 Deficient Mice - Nakano, Satoko (Public Library of Science, 2013)
Tax1-binding protein 1 (Tax1bp1) negatively regulates NF-κB by editing the ubiquitylation of target molecules by its catalytic partner A20. Genetically engineered TAX1BP1-deficient (KO) mice develop age-dependent inflammatory constitutions in multiple organs manifested as valvulitis or dermatitis and succumb to premature death. Laser capture dissection and gene expression microarray analysis on the mitral valves of TAX1BP1-KO mice (8 and 16 week old) revealed 588 gene transcription alterations from the wild type. SAA3 (serum amyloid A3), CHI3L1, HP, IL1B and SPP1/OPN were induced 1,180-, 361-, 187-, 122- and 101-fold respectively. WIF1 (Wnt inhibitory factor 1) exhibited 11-fold reduction. Intense Saa3 staining and significant I-κBα reduction were reconfirmed and massive infiltration of inflammatory lymphocytes and edema formation were seen in the area. Antibiotics-induced ‘germ free’ status or the additional MyD88 deficiency significantly ameliorated TAX1BP1-KO mice's inflammatory lesions. These pathological conditions, as we named ‘pseudo-infective endocarditis’ were boosted by the commensal microbiota who are usually harmless by their nature. This experimental outcome raises a novel mechanistic linkage between endothelial inflammation caused by the ubiquitin remodeling immune regulators and fatal cardiac dysfunction.